Spatial distribution of metals in the ICM: evolution of the iron excess in relaxed galaxy clusters. Issue 1 (23rd August 2018) - Liu, Ang; Tozzi, Paolo; Yu, Heng; De Grandi, Sabrina; Ettori, Stefano
ABSTRACT: We investigate the spatial distribution of iron in the intracluster medium (ICM) in a selected sample of 41 relaxed clusters in the redshift range 0.05 < z < 1.03 using Chandra archival data. We compute the azimuthally averaged, deprojected Z Fe profile of each cluster out to ∼0.4 r 500, and identify a peak in the distribution of iron followed by a flatter distribution at larger radii. Due to the steep gradient both in gas density and abundance, we find that the emission-weighted iron abundance within 0.2 r 500, which entirely includes the iron peak in most of the cases, is on average ∼25 per cent higher than the mass-weighted value, showing that spatially resolved analysis and accurate deprojection are key to study the evolution of iron enrichment in the very central regions of cool-core clusters. We quantify the extent of the iron distribution in each cluster with a normalized scale parameter r Fe, defined as the radius where the iron abundance excess is half of its peak value. We find that r Fe increases by a factor of ∼3 from z  ∼ 1 to z  ∼ 0.1, suggesting that the spatial distribution of iron in the ICM extends with time, possibly due to the mixing with the mechanical-mode feedback from the central galaxy. We also find that the iron mass excess within 0.3 r 500, when normalized to the total baryonic mass within the same region, does not evolve significantly, showing that this iron mass component is already established at z  ∼ 1.